Inland fisheries: A tool to eradicate ‘hidden hunger’ - Roy, Aparna (Journal of the Inland Fisheries Society of India, 2023)
Hunger and malnutrition is one of the worst disease that we are fighting today in a global scale to meet the sustainable development goals. India as a country is glorified from the revenue generated as a food exporter but shockingly it is a fact that India is ranked 71st out of 113 countries and 101 out of 116 countries in Global Food Security and Global Hunger Index. Food security is the most basic and important need for each living being but alone it doesn’t ensure about nutrition, whereas the micro & macro elements of quality food ensures a happy and healthy life through nutritional security. Different national programmes have been initiated by the Indian government to provide quality nutrition for the Indian Populace. Although even after all these efforts, hidden hunger is immerged one of the burning issues against maintaining the overall health of the Indian populace. Fish, not only a high source of protein but also minerals, trace elements, vitamins, fatty acids are essential for growth, immunity, metabolism and reproduction. These cheapest sources of protein can be the most probable solution to eradicate hidden hunger from Indian context, as India is the third largest fish-producing country and second in aquaculture production. Therefor fisheries play a crucial role in global and national economics by contributing in food and nutritional security.